Psychological Dynamics of Unmarried Adult Women in Sandwich Generations Families - Aryani Pamukti; Elok Halimatus Sa’diyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Adult women who are old enough but have not yet married in their families or communities in Indonesia are the targets of stigma. There are many factors that make women unmarried, some of which are due to being the breadwinner of the family (sandwich generation), focusing on work and career, continuing education, trauma, either from a partner or from past family experiences, and not having found the right partner. This research aims to explore the psychological dynamics of unmarried adult women in sandwich geenartion families. The research uses a qualitative analysis method with descriptive phenomenology to determine the psychological dynamics of unmarried adult women in sandwich generation families. The data collection method uses interview techniques for in-depth exploration and comprehensive observation of a phenomenon that is the object of research. The data sources in this research use primary data sources and secondary data sources. The psychological dynamics of unmarried adult women in generational sandwich families consists of three main loci, namely cognition, affection and conation which include multiple roles, pressure and social expectations towards them. This can include helping adult women find a balance between their roles, dealing with internal conflicts, and communicating their needs and expectations clearly to their families.